Large-scale fabrication of colloidal nano-sized CuCl solution with high concentration for using as fungicide for plant - Du, Bui Duy; Kim Dung, Lai Thi; Anh Tuan, Le Nghiem; Hien, Nguyen Quoc (Vietnam Journal of Chemistry, 2017)
Synthesis of nano-sized CuCl with Cu concentration from 4,000 to 6,000 ppm dispersed in chitosan solution (nano-sized CuCl/CTS) using CuSO4.5H2O as the precursor and NaHSO3 as the reducing agent in HCl acid medium on large scale of 1.000 kg/batch was carried out. The obtained nano-sized CuCl/CTS samples were characterized by transmission electron microscopy (TEM) and X-ray powder diffraction (XRD). Based on the obtained results, the reaction factors for fabrication of the colloidal nano-sized CuCl/CTS solution with Cu concentration of 5,000 ppm and CuCl nanoparticle size of about 7.7 nm dispersed in 1 % chitosan solution were selected for application in agriculture as a fungicide for plant protection. Keywords. Nano-sized CuCl, NaHSO3, HCl, chitosan.